Papers - Grinding and Classification - Importance of Classification in Fine Grinding (With Discussion) - J. V. N. Dorr; A. D. Marriott (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1930)
This paper reviews recent developments in the application of classification practice to the origination of fine-grinding flow sheets and traces the history of the mechanical classifier from its initial application for separating cyanide process sands and slimes down to its present six or more distinctly different applications at copper concentrators; it undertakes to show also, by reference to diagrammatic fine-grinding flow sheets and accompanying operating data from nine copper concentrators in western North America, the advantages gained from improved classi-ficiation flow sheets at these properties in terms of reduced grinding costs, improved flexibility of operation or increased recovery. Comparison is only made between different fine-grinding flow sheets at a given plant and no attempt is made to compare different concentrators, on account of ore variations and differences in metallurgical objectives sought,. The adoption of the flotation process in recent years, and especially the development of selective flotation, has brought a demand for much finer grinding than formerly. This has caused much thought to be given to grinding efficiency, and today there is hardly a mill where the grinding flow sheet is not under close study and subject to frequent changes. When closed-circuit grinding was introduced into metallurgy some years ago, its value was recognized at once, and since then the combination of mills and classifiers has been regarded and operated as a grinding unit. Apart from variations in both the grinding and classifying elements of this unit, there have been many variations in grouping tried by different mills to suit varying conditions of ore and plant limitations. Although operators feel that in most cases their present flow sheets are on trial, and the data on present work are often incomplete, we have felt that a discussion of the progress that has been made and an endeavor to show present trends and their results should be of use to the profession. We have therefore prepared flow sheets of some of the larger mills with which we have been in contact and present them with available data as to their results, in the hope that they may be of service now rather than later when practice may have become more standardized and more complete records and analyses have been made. We believe that the data given,